Digital Marketing Education for Islamic Entrepreneurship: A Systematic Literature Review - Muhammad Fadheel Djamaly (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The rapid advancement of digital technology has transformed entrepreneurship education, making digital marketing competencies increasingly essential for entrepreneurs in the digital economy. Simultaneously, Islamic entrepreneurship has gained growing attention because of its emphasis on ethical business practices, social responsibility, and Sharia-compliant economic activities. However, studies integrating digital marketing education and Islamic entrepreneurship remain fragmented. Therefore, this study aims to systematically review the existing literature by identifying publication trends, dominant research themes, methodological characteristics, research contributions, and future research directions. A Systematic Literature Review (SLR) was conducted using the PRISMA 2020 framework. Literature was retrieved from Google Scholar through Publish or Perish, yielding 348 initial records. After the identification, screening, eligibility, and inclusion stages, 18 studies published between 2020 and 2025 were selected for analysis. Bibliometric mapping using VOSviewer and qualitative synthesis were employed to interpret the findings. The results indicate a steady increase in research interest, with digital marketing emerging as the central theme linking entrepreneurship education, business development, digital innovation, and Islamic values. Digital marketing education contributes to strengthening digital competencies, entrepreneurial capabilities, and the integration of Islamic ethical values while supporting business sustainability and competitiveness. Nevertheless, the literature remains limited in theoretical integration, methodological diversity, and educational contexts. This review offers theoretical and practical implications for researchers, educators, curriculum developers, and policymakers while providing directions for future research on sustainable Islamic entrepreneurship.